"I didn't want to do, but I am happy to now!" Affect, voice and in-role performance. Issue 5 (27th June 2020) - Zhang, Zhenduo; Xiao, Huan; Gou, Xueqin; Li, Miaomiao; Zheng, Junwei
Abstract : Purpose: Previous research has examined the effects of discrete affects on voice; however, the role of trait and state affects in voice literature has received little attention. This study aims to address this important issue from a conservation of resources perspective, by exploring the influence of daily positive affect and emotional resistance to change on the voice of employees and their resulting work outcomes. Design/methodology/approach: The study collected data about 285 daily episodes from 57 employees over five consecutive days, using an experience sampling method (ESM) through mobile surveys. The study found that emotional resistance to change was negatively related to employee voice and in-role performance. Findings: Voice mediated the negative relationship between emotional resistance to change and in-role performance. The study also found that daily positive affect buffered the negative effects of emotional resistance to change on voice. Originality/value: These findings extend the research concerning affect and voice; the study provides integrative insight into how affect dynamically influences organizations.